2014
DOI: 10.1177/0022034514552675
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of SHED Prevents Bone Loss in the Early Phase of Ovariectomy-induced Osteoporosis

Abstract: Stem cells from human exfoliated deciduous teeth (SHED) are a unique postnatal stem cell population, possessing multipotent differentiation capacity and immunomodulatory properties. However, the mechanism by which SHED treat immune diseases is not fully understood. Here we show that systemic transplantation of SHED via the tail vein ameliorates ovariectomy (OVX)-induced osteopenia by reducing T-helper 1 (Th1) and T-helper 17 (Th17) cell numbers in the recipient OVX mice. Mechanistically, SHED transplantation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(122 citation statements)
references
References 41 publications
4
118
0
Order By: Relevance
“…According to reported data, systemically transplanted MSCs rescue bone loss through either circulatory immunomodulation/anti-inflammation 7 or local effects via homing to recipient bone marrow post infusion 8, 9. In this study, we confirmed that infused MSCs existed in recipient circulation for less than 24 h by using MSCs from GFP-transgenic donor mice (Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…According to reported data, systemically transplanted MSCs rescue bone loss through either circulatory immunomodulation/anti-inflammation 7 or local effects via homing to recipient bone marrow post infusion 8, 9. In this study, we confirmed that infused MSCs existed in recipient circulation for less than 24 h by using MSCs from GFP-transgenic donor mice (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Current pre-clinical studies have confirmed therapeutic effects of MSCs in ovariectomy (OVX)-induced bone loss 7, 9, 30-33, in which estrogen deficiency exerts pathologic effects through immunologically mediated mechanisms 34, as shown by our findings that administration of Tumor necrosis factor-alpha (TNF-α) neutralizing antibody could rescue OVX-induced skeletal defects 35, 36. Furthermore, immunomodulatory/anti-inflammatory capacity of MSCs has been recognized as an underlying principle for MSC-mediated therapy in OVX-induced osteopenia 7. Type 1 diabetes (T1D) is also recognized as a chronic autoimmune disorder characterized by hypoinsulinemia and hyperglycemia 37-39, which develops severe bone loss with endogenous MSC impairments 23, 40, 41.…”
Section: Introductionmentioning
confidence: 99%
“…FasL/Fas interactions play an important role in the regulation of the immune system [22, 24]. Previous scholars demonstrated that MSCs (BMSCs or SHED) may induce T-cell apoptosis, which further upregulates the Tregs via a high level of macrophage-released TGF-β, and results in immune tolerance [22, 25]. In this study, we isolated FasL mutant GMSCs from B6Smn.C3-FasL gld /J mice (FasL -/- GMSC).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, acetylsalicylic acid has been reported to improve SHED immunomodulation by elevating telomerase activity [48]. Systemic infusion of SHED ameliorates the osteoporotic phenotype in ovariectomized (OVX) mice by rescuing OVX-induced impairment of BMSCs, while also inhibiting osteoclastogenesis induced by activated T cell apoptosis in OVX mice via activation of the Fas-ligand-mediated Fas pathway [49]. It has also been reported that porcine and human SCAP suppressed T cell proliferation through an apoptosis-independent mechanism in vitro, while human DFCs stimulated with agonists of Toll-like receptor (TLR) 3 or TLR4 exhibited more effective suppression of PBMNC proliferation [46,50,51].…”
Section: Dental-tissue-derived Stem Cellsmentioning
confidence: 99%